Модули солнечных элементов на основе тандемных гетероструктур GaAs–InGaAs–AlGaAs - Krukovskiy, S. I.; Nikolayenko, Yu. E. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The fabrication and investigation of solar cell modules based on GaAs-InGaAs-AlGaAs heterostructures are reported. The active area of the module, assembled from twelve converters with dimensions of 10×20 mm, was 21.12 cm2. Under AM 1.5 spectral conditions, the measured efficiency of the module reached 28.5%, with a maximum output power of 602 mW.